THE PSYCHOEMOTIONAL STATUS OF ELDERLY PATIENTS WITH HYPERTENSION AND DIABETES MELLITUS - Normatov Murodjon Buribayevich (Journals Park Publishing, 2024)
Depression is an important general medical problem faced not only by psychiatrists, but also by doctors of other specialties, primarily therapists, neurologists, and cardiologists. This is due to the fact that manifestations of depression due to the severity of somatovegetative symptoms are often associated by patients not with a mental disorder, but with various somatic diseases. The frequency of depressive spectrum disorders turned out to be comparable with such a common disease in the Uzbek population as arterial hypertension. Materials and methods of research: The study was conducted on the basis of one of the city polyclinics. 134 patients with a previously diagnosed hypertension of stage III, grade 1-2, risk 4, concomitant type 2 diabetes mellitus, non-insulin dependent were studied (250 invitations were sent out, the response was 53.6% - 134 patients). Results and discussion: The average age of the patients was 67.9±4.6 years, the duration of the disease was on average 9.9±3.4 years. There were 63 men (47.0%) and 71 women (53.0%) among the surveyed. According to social status, patients were distributed: unemployed (pensioners) – 81.3%, employed – 18.7%. When assessing family status, 73.9% were single, and 26.1% live in families. The stress factor in the family is noted by more than 30%. Among the working population, 55.7% of patients have a work-related stress factor. Conclusions: Anxiety conditions were detected in 79% of the elderly, depressive – 68.7%, the frequency of TDS in patients increases with age. Female persons are more prone to psychoemotional disorders. The detection of TDS in patients with hypertension and concomitant type 2 diabetes mellitus is a prognostically unfavorable sign and a risk factor for the progression of the studied diseases. The severity of diabetic retinopathy correlates with increased levels of depression.
Keywords: arterial hypertension, diabetes mellitus, psychoemotional status.